Ethylene biosynthesis and signal transduction during ripening and softening in non-climacteric fruits: an overview - Liu, Meiying; Wang, Chaoran; Ji, Hongliang; Sun, Maoxiang; Liu, Tongyu; Wang, Jiahao; Cao, Hui; Zhu, Qinggang (Frontiers in Plant Science, 2024)
In recent years, the ethylene-mediated ripening and softening of non-climacteric fruits has been widely mentioned. In this paper, recent research into the ethylene-mediated ripening and softening of non-climacteric fruit is summarized, including the involvement of ethylene biosynthesis and signal transduction. In addition, detailed studies on how ethylene interacts with other hormones to regulate the ripening and softening of non-climacteric fruits are also reviewed. These findings reveal that many regulators of ethylene biosynthesis and signal transduction are linked with the ripening and softening of non-climacteric fruits. Meanwhile, the perspectives of future research on the regulation of ethylene in non-climacteric fruit are also proposed. The overview of the progress of ethylene on the ripening and softening of non-climacteric fruit will aid in the identification and characterization of key genes associated with ethylene perception and signal transduction during non-climacteric fruit ripening and softening.